Successful artificial reproduction of the African carp: Labeo parvus Boulenger, 1902 (Pisces: Cyprinidae) - Elie Montchowui; Clément A. Bonou; Philippe Lalèyè; Jean-Claude Philippart4; Pascal Poncin (Advances in Aquaculture and Fisheries Management, 2018)
The effectiveness of hormonal treatments to induce gamete emission in Labeo parvus was investigated in two spawning seasons (2007 and 2008). Brood fishes measuring 15 to 30 cm were gill netted in the Ouémé River (Benin) during their migration to their spawning habitat and then held in captivity (ponds). Captive fish (N = 30 males and N = 37 females) were treated with GnRHa combined with a dopamine antagonist during their natural spawning season from July through October. Ovulation was stimulated in four experimental groups of females by injecting Dagin (0.2 to 0.3 mlkg−1 body weight) and Ovaprim (0.5 to 0.6 mlkg−1 body weight). No female ovulated either in the groups receiving normal (as recommended by the manufacturers) dose injections of Dagin and Ovaprim (0.2 and 0.5 mlkg−1 body weight respectively) or in the group treated with a Dagin injection of 0.3 mlkg−1 body weight. Successful ovulation was only obtained with Ovaprim in the group treated with 0.6 mlkg−1 body weight. Latency times ranged from 10 to 14 h after hormone injection. L. parvus eggs were nonadhesive and transparent at ovulation. Fertilisation rates ranged from 74.0 to 97.7%. Hatching occurred after 10 to 14 h of incubation at 27 to 30°C and lasted 5 to 7 h. Hatching rates ranged from 70.0 to 83.3%. Larvae were 3.0 ± 0.4 mm long (total length) at hatching. In the two reproductive seasons, fertilisation rates and hatching were not significantly different (P > 0.05). The water temperature was shown to significantly affect spawning latency and incubation time. Our study demonstrated that captive L. parvus could be successfully induced to produce sperm and ova using injection of a synthetic gonadotropin-releasing hormone coupled with a dopamine antagonist (Ovaprim). Their ova could also be artificially fertilised in an experimental hatchery at water temperatures ranging from 27 to 30°C. The results obtained indicate that Ovaprim is the most effective agent for inducing artificial reproduction in L. parvus.